2020
DOI: 10.1051/epjconf/202022506006
|View full text |Cite
|
Sign up to set email alerts
|

Compton imaging reconstruction methods: a comparative performance study of direct back-projection, SOE, a new Bayesian algorithm and a new Compton inversion method applied to real data with Caliste

Abstract: Compton imaging is one of the main methods to localize radioactive hotspots, which emit high-energy gamma-ray photons, above 200 keV. Most of the Compton imaging systems are composed by at least two detection layers or one 3D position sensitive detector. In this study, we demonstrate the application of a new miniature pixelated single plane detector to Compton imaging. In this configuration, we do not have the information on interaction depth but we successfully test its ability to perform Compton localization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…However, the convergence speed of the adopted iterative reconstruction method was not sufficiently high because the imaging algorithms considered the high-energy γ-ray source located at a far distance, and the simulation programs developed at that time considered the simple detector system. Some studies have recently been conducted to improve the MLEM and compare it with other imaging models, with a focus on the application of Compton cameras in nuclear medicine and particle therapy [ 81 , 210 , 211 , 212 , 213 ]. Yabu et al [ 214 ] reported the superiority of the LM-MLEM method over SBP using a Si/CdTe Compton camera.…”
Section: Image Reconstruction Methods For Compton Imagingmentioning
confidence: 99%
“…However, the convergence speed of the adopted iterative reconstruction method was not sufficiently high because the imaging algorithms considered the high-energy γ-ray source located at a far distance, and the simulation programs developed at that time considered the simple detector system. Some studies have recently been conducted to improve the MLEM and compare it with other imaging models, with a focus on the application of Compton cameras in nuclear medicine and particle therapy [ 81 , 210 , 211 , 212 , 213 ]. Yabu et al [ 214 ] reported the superiority of the LM-MLEM method over SBP using a Si/CdTe Compton camera.…”
Section: Image Reconstruction Methods For Compton Imagingmentioning
confidence: 99%
“…For events with ≥2 triggered pixels, we can use Compton imaging to suppress events which cannot possibly come from the γ-ray optics. 77,78 A possible design optimization is the use of "staggered detector layers" in which the layers are offset slightly to reduce the loss of photons that hit the gaps of the detector assembly. A full tradeoff study that accounts for the gain of detected photons but also evaluates the effect on the energy resolution is outside the scope of this paper.…”
Section: Simulations Of the Focal Plane Detectormentioning
confidence: 99%
“…For events with ≥2 triggered pixels, we can use Compton imaging to suppress events which cannot possibly come from the γ-ray optics. 70,71 7 Predicted performance of a balloon-borne 511-CAM mission One of the key elements of the detector response is the instrument efficiency or effective area, which, for the 511-CAM, consists of both lens and detector efficiency. The simulation code calculates the channeling efficiency by using the relation…”
Section: Simulations Of the Focal Plane Detectormentioning
confidence: 99%